Arctic Ocean 2016 - Screenshots from Marine Radar Operator Station - Skarbø, Runa (The Norwegian University of Science and Technology (NTNU), 2023)
This dataset contains data collected during the Canadian-Swedish expedition Arctic Ocean 2016. The research cruise took place August through September 2016, using the icebreaker Oden.

For ship data from the cruise, as well as graphics and files describing the route, see https://snd.gu.se/sv/catalogue/study/ecds0221

For descriptions of Work Packages and research conducted during the cruise, see the SWEDARCTIC Arctic Ocean 2016 Expedition Report: http://urn.kb.se/resolve?urn=urn:nbn:se:polar:diva-3475

Additional information on the expedition, including links to publications, is available at http://www.polarforskningsportalen.se/en/arctic/expeditions/arctic-ocean-2016

Work Package: Ice Management

Screenshots were collected from the marine radar display of Oden. The images are used as input to an algorithm that estimates the local ice drift velocity. Images were collected during drifting periods and periods of low speed transit along the sailing track of the vessel. The screenshots cover the screen from the radar operator station. The frequency of the screenshots was between 0.2 and 1 Hz. The spatial resolution is between 3 to 6 nautical miles, depending on the current radar operator settings. The screenshots have a resolution of 1920 x 1200 pixels.

Data include:

Image files of the radar operator station screen.

Data insamlade under den svensk-kanadensiska expeditionen Arctic Ocean 2016, med forskningskryssningen Oden.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0241
Arctic Ocean 2016 - Skärmbilder från marin radarstation
Keywords: OCEANS; SEA ICE MOTION; The icebreaker Oden; Isbrytaren Oden; Natural Sciences; Naturvetenskap; Oceans; Kust och hav